Criteria for selecting sentinel unit locations in a surveillance system for vector-borne disease: A decision tool - Camille Guillot; Camille Guillot; Camille Guillot; Catherine Bouchard; Catherine Bouchard; Cécile Aenishaenslin; Philippe Berthiaume; Philippe Berthiaume; François Milord; Patrick A. Leighton; Patrick A. Leighton (Frontiers Media S.A., 2022)
ObjectivesWith vector-borne diseases emerging across the globe, precipitated by climate change and other anthropogenic changes, it is critical for public health authorities to have well-designed surveillance strategies in place. Sentinel surveillance has been proposed as a cost-effective approach to surveillance in this context. However, spatial design of sentinel surveillance system has important impacts on surveillance outcomes, and careful selection of sentinel unit locations is therefore an essential component of planning.MethodsA review of the available literature, based on the realist approach, was used to identify key decision issues for sentinel surveillance planning. Outcomes of the review were used to develop a decision tool, which was subsequently validated by experts in the field.ResultsThe resulting decision tool provides a list of criteria which can be used to select sentinel unit locations. We illustrate its application using the case example of designing a national sentinel surveillance system for Lyme disease in Canada.ConclusionsThe decision tool provides researchers and public health authorities with a systematic, evidence-based approach for planning the spatial design of sentinel surveillance systems, taking into account the aims of the surveillance system and disease and/or context-specific considerations.